A Critical Assessment of the Role of Religion Towards Peaceful Coexistence in Nigeria - Ottuh, Peter. O. O.; Onimhawo, John A. (PINISI Discretion Review, 2020)
Every human society is pruned to one kind of crisis or the other. Nigeria as a nation is not exempted. In Nigeria since her independence in 1960, it has been bedeviled with one crisis or the other, among which are ethnic, political and religious crisis. To resolve these crises, different methods of conflict resolution have been employed without lasting success. This paper is a critical examination of the functions of religion in ensuring peaceful coexistence in Nigeria. From the earliest time of human existence on earth, humans in every generation have encountered divergence typology of religious experiences which makes man to be pruned to experience more. Looking at it from a sociologically perspective, religion is a complex phenomenon that is mixed with culture yet, constituted by cultic practices of rituals and worship; and also, of a doctrine and an institutional organization. The dogmatic sphere of a given religion is inevitably difficult to ascertain, because it consists of a complicated and expansive system of beliefs that are organized throughout the generations of believers. The findings of this research have shown that the problems of religious disharmony, disunity, intolerance and non-peaceful coexistence among the numerous adherents of religions in Nigeria can be resolved by the positive roles religion plays. The paper concludes that Nigeria as a country has reached a philosophical and historical epoch where it is necessary to abandon the negative and anachronistic aspects of her culture and religion and integrate the positive elements of religion.